COMUNIDADE LGBTI+ E POLÍTICA ELEITORAL: ANÁLISE DE SEIS CANDIDATURAS NAS ELEIÇÕES 2024, NA CIDADE DE FORTALEZA–CEARÁ. - Lopes Oliveira, Marcos Heleno; de Oliveira Henrique, Victor Hugo (Suffragium - Scientific Journal of the Regional Electoral Court of Ceará (TRE-CE), 2026)
This research emphasizes the possible connections between the LGBTI+ community and electoral politics. The analysis of four candidacies for councilor in the 2024 elections, in the city of Fortaleza, in the State of Ceará, is taken as a reference. It follows that the problem considered by the research is aimed at revealing how engagement is going and what possible intolerances and prejudices are intricate within the reality of the electoral campaign of people identified as belonging to sexual and gender diversity. The main objective is to try to understand a little more about how the process of bringing together the electoral campaign and the LGBTI+ community takes place, focusing on the election for City Council. The aim is also to verify the campaign agendas of the people observed and consider the existence of proposals for the benefit of the group to which they belong and society in general.